Statistical Analysis of Separation Distance Between Equatorial Plasma Bubbles Near Suvarnabhumi International Airport, Thailand - Bumrungkit, Acharaporn; Supnithi, Pornchai; Saito, Susumu (My University, 2018)
Ionospheric disturbances can lead to the major detrimental effects on the availability of ground-based augmentation system. In low-latitude regions, equatorial plasma bubbles (EPBs) frequently arise. They originated from the bottom side of the ionosphere with the electron density inside the plasma bubbles lower than the outside area. It is well known that the EPB causes the strong fluctuation on Global Positioning System signals when passing through the ionospheric disturbed regions. Sometimes the EPBs may have more than one front. To better understand the ionospheric anomaly effect on ground-based augmentation system efficiency, the separation distance between EPBs needs to be studied. In this work, we analyze the slant total electron content from dual-frequency Global Positioning System receivers near Suvarnabhumi International Airport, Thailand, to ascertain the EPB occurrence. The distance between observed EPBs is computed based on the Haversine formula technique. The results found that the estimated separation distances between depletions on disturbed days in 2015 are in the range of 100 to 1,200 km.
Keywords: equatorial plasma bubble; ionosphere; separation distance; slant total electron content